(untitled) (Fiep Bulletin - online, 2013)
Traffic accidents (TA’s) are responsible for an elevated number of deaths, as well as for the increase in their victims’ morbidity, all around the world. For this reason, previous knowledge of variables that characterize these events in society is deemed essential for the establishment of adequate actions and prognosis. This article’s objective is to characterize TA’s according to the type of motor vehicle most often involved in the accident, type of public road use and the most often identified accident. It’s a descriptiveexploratory study, quantitative with prospective data, performed in the Hospital Monsenhor Walfredo Gurgel hospital complex, in the polytrauma, reanimation and ICU units as well as other clinics where TA victims were interned. The population consisted of 605 TA victims, between the months of November 2007 and January 2008. The data was analyzed by descriptive statistics and presented in the form of tables. TA’s are characterized with motorcycles, on their own, as the type of vehicle most often involved (53.2%); as for the type of public road user most often affected, motorcycle drivers were predominant, adding up to 61.3%. Among these, 88.4% were male and 11.6% female; regarding the type of accident, there was a predominance of collisions (61.8%). We expect this study to contribute to the formulation of a strategy for facing these events, as well as to give instruments for emergency professionals in the attending to severely injured victims, providing an estimate as to these individuals’ prognosis.